(untitled) (Journal of Applied Learning and Teaching, 2024)
This research paper explores the perceptions and adoption of AI chatbots by graduate students in Zimbabwean universities. The study aims to understand the potential benefits and challenges of adopting AI chatbots in the education sector and its impact on developing higher-order cognitive skills. The study used qualitative methodologies, including field interviews, to analyze the data. The findings suggest that graduate students have a positive attitude towards AI chatbots because they enhance their learning experience, enable them to overcome skill gaps, and aid in test preparation. Furthermore, the study revealed that AI chatbots foster the development of higher-order cognitive skills by augmenting traditional lectures, test preparation, and personalization. However, challenges include plagiarism, outdated information, and financial constraints associated with AI chatbots. The study recommends that AI companies offer discounts to graduate students to enable them to access AI chatbot tools and that universities develop referencing systems allowing students to acknowledge using AI chatbots as sources.